Letter - Winstanley, E.
027-0065-001 Telegraphic Address: INLAND-"WHOLESALE, MANCHESTER." FOREIGN-"COPEXPORT, MANCHESTER." TELEPHONE: DEANSGATE 5041. EXTENSION NO. 12. BLACKFRIARS 1212. PLEASE ADDRESS YOUR REPLY CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. CABLE CODES: A.B.C. 6TH AND 7TH EDITIONS; WESTERN UNION 8 LETTER; BENTLEY COMPLETE PHRASE; BENTLEY SECOND PHRASE; A.1. MARCONI, AND PRIVATE. Our Reference: EXPORT.2968.ST/RN. Your Reference: HVT/EAB. 12th September, 1939 The Trades Union Congress, Transport House, Smith Square, LONDON S.W.1. Dear Sirs, We beg to advise having sent forward by the s.s. C.W.S. PROGRESS, from Garston on the 8th instant, a further 56 parcels of Clothing, on account of the Federation Syndicale Internationale, Rouen. We attach hereto our invoice for freight, which also includes a small item for rent, amounting to 4/4d., charged by the Railway Company at Garston for previous consignments. Yours faithfully, E. Winstanley Export Department. O.K. See C.W.S. letter 15/9/39 EAB 292/946/27/65